Pengaruh Kinerja Guru Terhadap Tanggung Jawab Belajar Siswa pada Pembelajaran Matematika di SMP - Rahmatia Rahmatia; Hidayat Hidayat (Jurnal Akademik Pendidikan Matematika, 2022)
This reseach aimed to determine the effect of teacher performance on student learning responsibilities in learning Mathematics in VIII grade of SMP Negeri 1 Siompu Barat. This reseach was a quantitative research with Ex-Post Facto method. Data collection using questionnaires and documentation. The data analysis techiques used prerequesite test, with simple correlation and regression analysis. Hypothesis testing technique using regression analysis. Based of the results of data analysis and simple regression astimates, techer performance assessment (X) on learning responsibility (Y) produced a significance value of  0.018 < 0.05. So that there was an effect of techer performance (independent  variable) on learning responsibility (bound variable). SPSS output results also produced  was 0.123. This showed  that the magnitude of the in fluence of teacher performance on learning responsibilities was as much as 12.3%. According to the equation of the formulation of the simple regression analysis was Y = 133.339 + 0.136X, it coult be seen that the teacher performance variable at the 1% level was better, the student’s learning responsibity would increasi by 0.316. Thus, based on the hypothetical decision that the hypothetical desicion taht coult be responsibilities in learning mathematics VIII grade of SMP Negeri 1 Siompu Barat.